Isu-isu Masyarakat terhadap Pembangunan Rumah Ibadah di Desa Laut Dendang Percut Sei Tuan Studi Kasus Gereja di Desa Laut Dendan - Lubis, Ahmad Khujaini (ANWARUL, 2023)
Laut Dendang Village, a village located on Jalan Tegal Sari Dusun IX Kenanga, Percut Sei Tuan District, is a village where 80% of the people adhere to Islam and 20% of Christians. Issues are something that is contradictory or that creates polemics about a person or an organization. Issues can appear in the form of opinions, namely statements that can be conveyed through words. Society is a group of individuals who live together, work together to obtain common interests that already have an order of life, norms and customs that are adhered to in their environment. According to the Big Indonesian Dictionary (KBBI), a house of worship is a place used by religious people to worship according to religious teachings or beliefs. Houses of worship are buildings that have certain characteristics that are specifically used for worship for adherents of each religion on a permanent basis, excluding family places of worship. The research method used by researchers is the anthropological approach. While the theory approach is comparative theory. This type of research conducted by researchers is qualitative research. The research findings are that Islam is the majority religion in Laut Dendang Village. Data collection techniques in this study with observation, interviews and documentation. The results of this study show that the people of Laut Dendang Village partially agree that the construction of a house of worship is very significant, because it relates to religious harmony. The people of Laut Dendang Village who do not agree with the construction of a house of worship can lead to conflict because they do not get the support of the local community, who in the majority have a different religion from the owners and users of the house of worship. The conclusion of this research is that the establishment of worship is a place used by religious people to worship according to the teachings of their respective religions or beliefs. Houses of worship for every religion are centers of activity and culture. Therefore, the existence of houses of worship is a necessity for every religious community.